The promotion effect of Sb on the Na resistance of Mn/TiO2 catalyst for selective catalytic reduction of NO with NH3. (1st April 2016) - Yang, Ning-zhi; Guo, Rui-tang; Pan, Wei-guo; Chen, Qi-lin; Wang, Qing-shan; Lu, Chen-zi
Graphical abstract: Highlights: Mn–Sb/TiO2 catalyst shows higher NH3 -SCR activity and wider temperature window than Mn/TiO2 catalyst. Mn–Sb/TiO2 catalyst has much better Na-resistance than Mn/TiO2 catalyst. The addition of Sb on Mn/TiO2 catalyst can improve its low-temperature reducibility. The addition of Sb on Mn/TiO2 catalyst can generate strong Lewis acid sites for NH3 adsorption. Abstract: Na has a serious deactivation effect on Mn/TiO2 catalyst for selective catalytic reduction of NO with NH3 . In this study, it was found that Sb had a promotion effect on the Na resistance of MnOx/TiO2 catalyst. Then the promotion mechanism was investigated based on the characterization results of BET, XRD, H2 -TPR, NH3 -TPD, XPS and in situ DRIFT. The results of H2 -TPR and NH3 -TPD showed that the addition of Sb on MnOx/TiO2 could enhance the redox ability and surface acidity respectively, and the results of DRIFT indicated that the addition of Sb on MnOx/TiO2 could generate strong Lewis acid sites on the catalyst surface for NH3 adsorption. Therefore, the doping of Sb has a promotion effect on the Na resistance of Mn/TiO2 catalyst.